Pengaruh Model Discovery learning terhadap Hasil Belajar Kelas V UPTD SD Negeri 28 Parepare - Natriani Syam; Muslimin Muslimin; Nabila Khaerunnisa Rusman (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine whether there is an influence of the Discovery learning learning model on student learning outcomes in class V UPTD SD Negeri 28 Parepare. This research is a research that uses a quantitative approach to the type of experimental research and the design used is a non-equivalent control group design and a quasi-experimental form. The type of sampling technique used was purposive sampling with a total sample of 40 students. The outcome data in this study are the results of the pretest and posttest. Data analysis techniques are descriptive data analysis and inferential data analysis. The results of descriptive statistiks were obtained from student learning outcomes in the matter of changes in the shape of objects. The results of the analysis using the independent sample t-test showed that the tested value was less than 0.05, namely 0.042 <0.05. Sig. (2-tailed) < 0.05 or 0.042 < 0.05, which means that H0 is rejected and H1 is accepted. Thus it can be concluded that the Discovery learning learning model has an effect on student learning outcomes on material changes in the form of objects class V UPTD SD Negeri 28 Parepare.